l tempo della memoria e la memoria del tempo. Una prospettiva ebraica - Ricci Sindoni, Paola (Bollettino Filosofico, 2016)
No doubt the memory, with its rituals devices and its practical forms – symbolic, represents Judaism a huge patrimony of narrative knowledge and foundation of his religious and civic identity. This paper aims to cover certain stages of Jewish thought, which thematizes the paradigm of temporality, understood as a virtuous circularity between the sacred and the profane, between time and eternity, so that the time of memory is requalifying as a memory of time. In this perspective it is certainly not just the time spent -place usually connected to the memory- to generate the heart of this. It’s rather the future, with its messianic charge, to reclaim the memory and history, whenever the Jew - and every man - neutralizes the vacuum time and corrosive of today by opening it to redemption. In this sense is the future time of the memory.